Financing Global Common Goods for Health: When the World is a Country - Gavin Yamey; Dean Jamison; Odd Hanssen; Agnès Soucat (Taylor & Francis Group, 2019)
"Global functions" of health cooperation refer to those activities that go beyond the boundaries of individual nations to address transnational issues. This paper begins by presenting a taxonomy of global functions and laying out the key value propositions of investing in such functions. Next, it examines the current funding flows to global functions and the estimated price tag, which is large. Given that existing financing mechanisms have not closed the gap, it then proposes a suite of options for directing additional funding to global functions and discusses the governance of this additional funding. These options are organized into resource mobilization mechanisms, pooling approaches, and strategic purchasing of global functions. Given its legitimacy, convening power, and role in setting global norms and standards, the World Health Organization (WHO) is uniquely placed among global health organizations to provide the overarching governance of global functions. Therefore, the paper includes an assessment of WHO's financial situation. Finally, the paper concludes with reflections on the future of aid for health and its role in supporting global functions. The concluding section also summarizes a set of key priorities in financing global functions for health.